2011
DOI: 10.1016/j.earlhumdev.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia: Novel approaches for premature infants

Abstract: Hypothermia for hypoxic ischemic encephalopathy has recently permeated clinical practice for term infants. Speculation regarding a neuroprotective benefit of hypothermia for premature infants with HIE has been raised as a need for further research. Hypothermia for other indications including necrotizing enterocolitis with the hope of tissue preservation following injury is less well studied. A summary of evidence for hypothermia and premature infants is presented in this brief report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…C. elegans is a free living soil nematode that prefers environments with oxygen concentrations ranging between 5 and 12% [4], [7]. Specific oxygen sensing neurons are activated and drive the animal’s response to a preferred envionrment.…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans is a free living soil nematode that prefers environments with oxygen concentrations ranging between 5 and 12% [4], [7]. Specific oxygen sensing neurons are activated and drive the animal’s response to a preferred envionrment.…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic approaches to counteract the effects induced by ROS during hypoxia/ischemia and especially reoxygenation have been proposed. However, no neuroprotective agent has been proven safe and effective in the protection of neonates from neurological sequels following an ischemic insult beside hypothermia in some specific cases [21]. Therefore, it is essential to gain more insights into biochemical and cellular mechanisms of neuronal injury induced by PA to identify potential therapeutic targets, compounds and strategies [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of large RCTs have shown that reduction of head or whole-body temperature to 3 degrees below normal for 3 days is associated with a 40 to 50 percent reduction in death and long-term disability in term infants with moderate or severe encephalopathy [5], with side effects that are readily manageable and usually of trivial clinical significance. Initiation of therapeutic hypothermia (TH) within 6 hours of birth has rapidly become the standard of care in many NICUs around the developed world [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Infants with HIE may be quite ill with neurologic dysfunction and multisystem organ failure. Roughly 60 percent of infants with HIE die or carry long-term neurologic impairment [5]; in the worst cases, infants are minimally interactive; require intensive support of breathing, circulation, and vital organ function; and are completely and permanently dependent on caregivers. …”
mentioning
confidence: 99%